THE RELATIONSHIP BETWEEN LANGUAGE AND SOCIETY - Muhammadjonova Madina Nozimjon qizi; Z.A. Umirova (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT This  article  investigates  the  complex  and  multifaceted  relationship  between language and society, emphasizing the ways in which language both shapes and reflects social identities, cultural values, and power structures. It explores key sociolinguistic concepts,  including  language  variation,  identity,  and  linguistic  inequality, demonstrating  the  crucial  role  that  language  plays  in  constructing  and  maintaining social realities. By examining the processes of language change and highlighting the importance of preserving linguistic diversity, the article argues for the dynamic and essential  nature  of  language  as  a  foundational  element  of  human  society,  deeply intertwined with the social, cultural, and political fabric of communities. Through this lens, the article aims to shed light on the ongoing transformations in language use and the significant impact these shifts have on the construction of identity, societal norms, and power relations. By analyzing language change and the importance of preserving linguistic diversity, the article emphasizes language as a dynamic and essential element of human society 1 .